أثر الإدمان على مواقع التواصل الاجتماعي على الاغتراب النفسي - مقدم, صافية (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى التعرف على أثر الإدمان على مواقع التواصل الاجتماعي على الاغتراب النفسي لدى تلاميذ السنة الثالثة ثانوي، كما سعت إلى الكشف عن الفروق الاغتراب النفسي تبعا لمتغيري الجنس والتخصص. أجريت الدراسة على عينة الدراسة مكونة من 90 تلميذاً وتلميذة اختيروا بطريقة عشوائية الذين طُبّق عليهم استخدام استبيان لجمع المعلومات يتكون من 25 بنداً. تم تحليل البيانات بواسطة برنامج أسبيس باستخدام اختبار "ت" لدلالة الفروق بين عينتين مستقلتين. توصلت النتائج إلى أن الإدمان على موقع التواصل الاجتماعي له أثر على الاغتراب النفسي لدى تلاميذ السنة الثالثة ثانوي، كما توصلت إلى وجود فروق ذات دلالة إحصائية في الشعور بالاغتراب النفسي حسب الجنس، في حين عدم وجود فروق ذات دلالة إحصائية في الاغتراب النفسي حسب التخصص، وتمت مناقشة النتائج في ضوء الإطار النظري وخصائص العينة. Abstract: The current study aimed to identify the effect of social network sites addiction on psychological alienation among third-year secondary school students, and also sought to reveal the differences in psychological alienation according to the gender and specialty. The study was administered to a sample of 90 students who were randomly selected, who were given a questionnaire to collect data consisting of 25 items. The data were analyzed by SPSS software using for t-test for two independent samples. The results revealed that addiction to the social network sites has an impact on psychological alienation among third-year secondary school students. Furthermore, the study showed significantly differences in the psychological alienation according to gender, while there were no significantly differences in psychological alienation according to specialty. The results were discussed in the light of the theoretical framework and the sample characteristics.
لدى تلاميذ السنة الثالثة ثانوي
مقال
Keywords: إدمان أنترنت؛ مواقع تواصل اجتماعي؛ اغتراب نفسي، تلاميذ ثالثة ثانوي; Internet addiction; social network; psychological alienation, secondary school students